2020
DOI: 10.1002/jcu.22965
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of measurements of facial profile parameters by operators with different levels of experience at 15 to 23 weeks of gestation

Abstract: Purpose: To compare the reliability of measurements of five fetal facial profile parameters by operators with different levels of experience, at 15 to 23 weeks of gestation in Thai fetuses.Methods: An observational study was conducted. The inferior facial angle, anteroposterior mandibular diameter, mandible width, maxilla width, and mandible length were measured in 123 normal fetuses, using 2D ultrasonography, by three operators with different levels of experience. Each participant was examined by two operator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…We evaluated four proposed parameters to determine normal mandible development both in size and position. At the beginning of this study, the values of each parameter from each sonographer were evaluated and resulted in moderate-to-excellent intra- and-inter-observer agreements [ 22 ]. The major limitation of our study was the incomplete measurement of some parameters due to poor fetal position or thick maternal abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated four proposed parameters to determine normal mandible development both in size and position. At the beginning of this study, the values of each parameter from each sonographer were evaluated and resulted in moderate-to-excellent intra- and-inter-observer agreements [ 22 ]. The major limitation of our study was the incomplete measurement of some parameters due to poor fetal position or thick maternal abdominal wall.…”
Section: Discussionmentioning
confidence: 99%
“…Our sonographic examination methods were based on the previous studies as mentioned in the exclusion criteria section [ 13 , 15 , 19 ], and are shown in Figs 1 to 5 . Before conducting the study, we standardized all operators for fetal facial profile measurements to ensure acceptable intra-and-interobserver variabilities [ 22 ]. In this study, each woman was examined by one of the three operators (PB or RS or CS) during which three measurements were taken for each parameter within a limited scanning time of 30 minutes.…”
Section: Methodsmentioning
confidence: 99%